Matrimonial property: Concept and ruling - Siraji, Ahmad Hussein Abdul Shakoor; Halim, Muhamad Mustakim Abdul (Linguistics and Culture Review, 2021)
This research studies matrimonial property, which is a marital financial right that was not discussed by classical scholars in their books; it is a new, contemporary issue. The problem of this research is that in most contemporary societies, the husband can no longer cover all the household expenses or improve the financial status of the family on his own, which results in the wife's going out for work and contributing to many expenses like the house, car, etc. Spouses may not pay attention to this matrimonial property; however, when marriage is terminated, disputes about it arise. This research offers answers about the concept of matrimonial property and its types; the ruling of this property and how it can be divided. It also elaborates on the definition of matrimonial property and the legality of claiming it. Thus, this research is divided into two sections: the first explains the matrimonial property and its types, and the second clarifies the ruling of the matrimonial property. The paper also includes an introduction and a conclusion that presents the research findings.